EFFECTIVE STRATEGIES FOR ORGANIZATIONAL CULTURE MANAGEMENT - Lisa, Jihana; Munaawaroh, Hayatul; Novaldi, Erwin; Sandra, Rizki Rudi; Hadiati, Eti; Elice, Deti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to understand the importance of organizational culture, analyze organizational culture and strategies to support and change culture. The method used is library research, collecting data by finding sources and reconstructing from various sources such as books, journals, and existing research. Organizational culture can have a major impact on organizational performance and success. Organizations with cultures that align with the goals and values of their members tend to create positive and productive environments. Conversely, cultural conflicts or mismatches between an organization's culture and its members' individual values can result in discomfort and lack of optimal performance. Therefore, the understanding and management of organizational culture is critical to the sustainability and success of an organization. Analyzing organizational culture is also a process that aims to understand how values, beliefs, and norms in the organization affect individual behavior and overall performance. This analysis is important to determine whether the organizational culture supports the company's strategic goals or needs to be changed. Changing and supporting organizational culture requires a strategic and sustainable approach, as organizational culture is embedded in long-standing behaviors, norms, and values.